Risk of Multiple Seizure Recurrence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The risk of multiple recurrences after an initial seizure recurrence was assessed in a prospective study of 407 children, followed for a mean of 9.6 years at Montefiore Medical Center, The Albert Einstein College of Medicine, NY, and in private practices.